9(3x-9)-7-2x=

Simple and best practice solution for 9(3x-9)-7-2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3x-9)-7-2x= equation:


Simplifying
9(3x + -9) + -7 + -2x = 0

Reorder the terms:
9(-9 + 3x) + -7 + -2x = 0
(-9 * 9 + 3x * 9) + -7 + -2x = 0
(-81 + 27x) + -7 + -2x = 0

Reorder the terms:
-81 + -7 + 27x + -2x = 0

Combine like terms: -81 + -7 = -88
-88 + 27x + -2x = 0

Combine like terms: 27x + -2x = 25x
-88 + 25x = 0

Solving
-88 + 25x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '88' to each side of the equation.
-88 + 88 + 25x = 0 + 88

Combine like terms: -88 + 88 = 0
0 + 25x = 0 + 88
25x = 0 + 88

Combine like terms: 0 + 88 = 88
25x = 88

Divide each side by '25'.
x = 3.52

Simplifying
x = 3.52

See similar equations:

| -7x^2+2x+14=0 | | -5w=-15 | | .25(12-8y)+6=9-2y | | N^2-2n-3=2n(n-3) | | 4x-2(3+x)=2(x+1)-x | | 10-6x=2(x-3) | | 2(3a+8)-11=7 | | x-(-7)=13 | | 6+3x=8+4x | | 3y+15+3y=30 | | 0.46666666666x-0.2=4 | | 1/37.5(1/2)= | | 4x-5x+3(x+4)= | | -16t^2+80t+60=0 | | 3w+3w=81-21 | | -6b(5a-3b)+7(-5ab-7b)= | | 17x-7=5+15x | | 16t^2+80t+60=0 | | 2-7(4-3/4)*6= | | x-8.4=-6.5 | | 4x-5+3(x+4)= | | 200m-100m+53,350=56,375-175m | | p+p+17+4p-34=799 | | 4w+2w=42 | | 3.8-0.6d=8.3+0.9d | | 8t^2+2t^2-3= | | n+(n+2)=116 | | 7y+12-y=48 | | 12x*2y-8x*2y*2+11x*2y-4x*3y*2-9xy*2= | | -(2x+y)-2(-x-y)= | | t+28=22 | | 13x*2y-8x*2y*2+11x*2y-4x*3y*2-9xy*2= |

Equations solver categories